ATTRITION IN FISHERWOMEN ACTIVITY GROUPS: A CASE STUDY ON THEERAMYTHRI, KERALA - Athira Reeja (International Scientific and Current Research Conferences, 2023)
This case study explores the phenomenon of attrition in fisherwomen activity groups, focusing on Theeramythri in Kerala, India. Fisherwomen activity groups play a crucial role in empowering women in the fishing communities by providing them with collective platforms for economic, social, and political engagement. However, attrition, or the decline in participation and sustainability of these groups, poses challenges to their effectiveness and long-term impact. This study aims to investigate the factors contributing to attrition in fisherwomen activity groups and its implications for women's empowerment. Data were collected through interviews, observations, and document analysis. The findings reveal various factors leading to attrition, such as family responsibilities, financial constraints, social stigmatization, and lack of resources and support. The study contributes to the understanding of attrition in fisherwomen activity groups and provides insights for designing strategies to enhance their sustainability and impact.